The impact of trade and macroeconomic policies on frontier deforestation - Wunder, Sven; Verbist, B. (ICRAF South East Asia, 2003)
The purpose of this lecture note is to summarise different research results about the impact of macro-level factors and “extra-sectoral” policies on tropical forest cover. Specifically, we are interested in the forest margins - i.e. the spatial transition zone between tropical forests and converted land uses. What are the policy factors that accelerate frontier expansion, and which ones tend to slow it down? The main objectives are: a. To learn how different changes related to trade and macroeconomic policies affect the loss of frontier forests, i.e. to understand both the likely direction and weight of these factors in influencing the speed of forest conversion; b. To comprehend trade-offs and synergies between policies for natural-forest conservation and those designed to promote economic development; c. To appreciate these linkages in the light of a few micro- and macro-level examples. A key finding is that what happens to tropical forests is more determined by events outside the forest arena than by what happens inside the forest sector. In other words, the extra-sectoral impacts will often be more important than, for instance, the new forest law, the participatory tree planting project or the environmental education programme that is implemented at the forest margins. That does not necessarily mean that forestry interventions are not effective. What it does mean is that some macroeconomic and extra-forestry factors tend to set the scene for success or failure of the projects and strategies of forest margin stabilisation, so that the promoters of these strategies need to have a realistic vision about the direction and proportions of impacts. In some cases, the macro decision makers should also explicitly take into account how forests are affected before they make their “extra-sectoral”, macro-level choices.